Examining the Academic and Non-Academic Correlates of Student Retention - Narzoles, Danebeth Tristeza Glomo-; Palermo, Donna Glomo- (International Journal of Publication and Social Studies, 2021)
This study was conducted to verify the reasons of students who had withdrawn or discontinued their studies. Academic and non-academic correlates of student retention were identified through the reasons provided by the students in the Withdrawal/Dropping Out Forms which are available at the Registrar’s Office. Moreover, telephone calls were done to further discuss the reasons for leaving the university. Majority of students who had withdrawn are males. In terms of program enrolled, there are many business students who dropped out from the university, followed by the international studies, engineering, computing, and lastly, the graduate students. Moreover, majority of those who dropped out are married, followed by single, divorced, and others who did not mention their status. On the other hand, there were more working students who had withdrawn from the university compared to non-working students. Among the reasons cited for leaving the university, the top five are experienced health-related problems, did not have enough money to continue, and accepted a fulltime job, conflict between demands of job and university, and visa problems. Reasons that were not cited at all are on the program/institutional issues such as dissatisfied with academic performance, could not connect classroom to the outside world, achieved academic goals, dissatisfied with the class size, dissatisfied with the learning environment, dissatisfied with the quality of teaching, and inadequate academic support.